Performance of tomato (Lycopersicon esculentum Mill.) germplasm to salinity stress - Siddiky, MA; Khan, MS; Rahman, Md Mostafizur; Uddin, M Khabir (Bangladesh Journal of Botany, 2018)
A solution culture experiment was conducted to screen out 16 Bangladeshi tomato germplasm for salinity tolerance with respect to severity of leaf symptoms, shoot and root dry matter production, fruit yield, shoot Na+, K+, Ca2+ accumulation and their respective ratios by exposing up to 120 mM NaCl. The salinity tolerance scale ranged from 1.0 (most tolerant) to 3.5 (most sensitive). Based on the severity of leaf symptoms, “BT14 (BARI Tomato 14)” and “BHT5 (BARI Hybrid Tomato 5)” were found to be most tolerant germplasm to salinity with score 1.0. Reduction of dry weight was found to be 19% (shoot) and 15% (root) in BT14 and BHT5, 30 - 76% (shoot) and 27 - 83% (root) in other germplasm. Higher correlation was found between salinity tolerance scale classes and the reduction of shoot/root dry weight, Na+ concentration, K+/Na+, and Ca2+/Na+ ratios in BT14 and BHT5 germplasm. The fruit yield of BT14 and BHT5 germplasm was less and decreases with high salinity. Thus, “BT14” and “BHT5” can be regarded as a breeding material for development of new tomato varieties resistant to salinity.